Death in Daliyyat Abi Alalá Al-Maarry and Milton’s "Lycidas": A Comparative Study - Hadi Saleh Sultan (PROSPECTIVE RESEARCHES, 2023)
This study sheds light on the nature of death, the anxiety and images associated with it in two elegies; “Daliat Abi Alálá El-Maárry” and Milton‟s „„ Lycidas‟‟. The first section deals with the nature of death and its comprehensiveness. It concentrates on the naturality and unnaturality of death as it is studied by some philosophers and then by the two poets. Then it tackles the poets' views concerning the comprehensivity of death which passes over everything in the universe. The second section is devoted to the anxiety of death and how this phenomenon is accompanied by death and is resulting from its facticity. In the last section different images of death and the fragility of the existence in the two elegies are studied; sometimes they come to be similar, other times they differ according to the environment, time and culture to which each poet belongs. The solace through immortality in both poems is also studied.